Brain Tumor segmentation and parsing on MRIs using multiresolution neural networks - Silvana Castillo, Laura; Alexandra Daza, Laura; Rivera, Luis Carlos; Arbelaez, Pablo (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2018)
Brain lesion segmentation is a critical application of computer vision to the biomedical image analysis. The difficulty is derived from the great variance between instances, and the high computational cost of processing three dimensional data. We introduce a neural network for brain tumor semantic segmentation that parses their internal structures and is capable of processing volumetric data from multiple MRI modalities simultaneously. As a result, the method is able to learn from small training datasets. We develop an architecture that has four parallel pathways with residual connections. It receives patches from images with different spatial resolutions and analyzes them independently. The results are then combined using fully-connected layers to obtain a semantic segmentation of the brain tumor. We evaluated our method using the 2017 BraTS Challenge dataset, reaching average dice coefficients of 89 %, 88 % and 86 % over the training, validation and test images, respectively.
Created from Fastlane, Scopus look-up
Keywords: Brain tumors; Deep learning; Machine learning; MRI; Semantic segmentation